Nanoelectrodes: Large‐Scale Nanoelectrode Arrays to Monitor the Dopaminergic Differentiation of Human Neural Stem Cells (Adv. Mater. 41/2015). (2nd November 2015) - Kim, Tae‐Hyung; Yea, Cheol‐Heon; Chueng, Sy‐Tsong Dean; Yin, Perry To‐Tien; Conley, Brian; Dardir, Kholud; Pak, Yusin; Jung, Gun Young; Choi, Jeong‐Woo; Lee, Ki‐Bum
Abstract : A large‐scale homogeneous nanocup‐electrode array (LHONA) capable of noninvasive real‐time monitoring of dopamine generation from human neural‐stem‐cell‐derived midbrain neurons is described by J.‐W. Choi, K.‐B. Lee, and co‐workers on page 6356. LHONA, fabricated through sequential laser interference lithography (LIL), is a conductive cell‐culture platform that is extremely important for electrochemically active biomolecule detection. LHONA is a reliable platform capable of detecting dopamine produced from cells in a quantitative manner.